KAJIAN POTENSI LAHAN BASAH MANGROVE SEBAGAI AGEN FITOREMEDIASI LOGAM BERAT DI DESA SUNGAI MUSANG - Puspita Dewi, Ira; Nursalam, Nursalam; Hamdani, Hamdani; Marista Salsabila, Anggi; Lestari, Putri (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2024)
Heavy metals such as lead (Pb), cadmium (Cd), and copper (Cu) are hazardous pollutants that often contaminate water bodies, especially in coastal areas. This study aims to evaluate the potential of mangrove wetlands in Sungai Musang Village as a natural phytoremediation agent to absorb accumulated heavy metals in aquatic sediments. The research was conducted at the Sungai Musang estuary, Banjar Regency, South Kalimantan, in 2024. Sampling and analysis methods used atomic absorption spectrometry (AAS) to detect heavy metal content in mangrove and non-mangrove areas. The study results showed that the concentrations of Pb, Cd, and Cu at all observation points were far below the limits set by Ontario (1993) and IADC/CEDA (1997) standards, indicating that the area is still safe from heavy metal pollution. Thus, the mangrove wetlands in Sungai Musang Village play a significant role in absorbing heavy metals from aquatic environments, making them a potential phytoremediation agent